Eduard Artem’ev and the Sonics of National Identity - Eliot Gelberg-Wilson (Slovo, 2016)
Download this article from UCL Discovery. National identity has a specific resonance in music, as well as in film. Music played a prominent role in the development of Rusia’s nineteenth century nationalist movements, while European trends such as Baroque and Classical have certain cultural codings from a Russian perspective. Exposition of national identity in Russian cinema has attracted significant interest. Over the 1970s and 1980s, many films gave ‘expression to the concerns, fears and hopes of the nationalists.’ The issue of national identity changes in post-Soviet cinema, seen, for example, in the essays compiled in Birgit Beumers’ Russia on Reels (1999). In studies on both periods, the films of three directors figure constantly — Andrei Tarkovsky, Nikita Mikhalkov and Andrei Konchalovskii. Artem’ev has worked on almost all of their films. This article will look at films by these three directors, as they are the films most relevant to national identity within Artem’ev’s canon.